Pregnancy experiences of Western Australian women attending a specialist childbirth and mental illness antenatal clinic - Hauck, Yvonne; Allen, S.; Ronchi, F.; Faulkner, D.; Frayne, J.; Nguyen, T. (Taylor & Francis Group LLC, 2013)
Our purpose was to explore the pregnancy experiences of Australian women attending a specialized Childbirth and Mental Illness (CAMI) antenatal clinic. A qualitative exploratory design was selected to give voice to women with a severe mental illness receiving antenatal care. Telephone interviews with 41 women, 24 primiparous and 17 multiparous, were analysed using thematic analysis. Three themes emerged: ‘Building relationships’, ‘Acknowledged me as a person with special needs’ and ‘Respect and understanding without stigma’. Findings offer insight into care experiences possible within a multidisciplinary model developed to addresses psychiatric and obstetric needs of pregnant women with severe mental illness.